Assessment and Teaching of 21st Century Skills: Methods and Approach - Griffin, Patrick (Springer, 2016)
This second volume of papers from the ATC21STM project deals with the development of an assessment and teaching system of 21st century skills. Readers are guided through a detailed description of the methods used in this process. The first volume was published by Springer in 2012 (Griffin, P., McGaw, B. & Care, E., Eds., Assessment and Teaching of 21st Century Skills, Dordrecht: Springer). The major elements of this new volume are the identification and description of two 21st century skills that are amenable to teaching and learning: collaborative problem solving, and learning in digital networks. Features of the skills that need to be mirrored in their assessment are identified so that they can be reflected in assessment tasks. The tasks are formulated so that reporting of student performance can guide implementation in the classroom for use in teaching and learning. How simple tasks can act as platforms for development of 21st century skills is demonstrated, with the concurrent technical infrastructure required for its support. How countries with different languages and cultures participated and contributed to the development process is described. The psychometric qualities of the online tasks developed are reported, in the context of the robustness of the automated scoring processes. Finally, technical and educational issues to be resolved in global projects of this nature are outlined.